The interconnection between social media addiction, alexithymia and empathy in medical students - Ursoniu, Sorin; Bredicean, Ana-Cristina; Serban, Costela Lacrimioara; Rivis, Ioana; Bucur, Adina; Papava, Ion; Giurgi-Oncu, Catalina (Frontiers in Psychiatry, 2024)
Introduction: This study explores whether high alexithymia values correlate with low levels of empathy, while also trying to identify potential connections with social media addiction. Methods: We hypothesized that alexithymia mediates the relationship between social media addiction and empathy levels in a sample of undergraduate students. The study population consisted of 649 medical students in the 4th/5th/6th University year, recruited between March and May 2021. For this assessment, we employed three psychometric instruments: the Toronto Empathy Questionnaire (TEQ), the Social Media Addiction Scale-Student Form (SMAS-SF), and the Toronto Alexithymia Scale (TAS-20). A pathway analysis investigated alexithymia as a mediator between social media addiction and the degree of empathy in medical undergraduates. Sobel's test and the Baron and Kenny approach were used for testing mediation. Results: The TEQ total mean score was 48.76±5.65, while the TAS-20 total mean score was 47.71±11.49. Further analysis of the TAS-20 scale scores showed that 21.42% of students had possible alexithymia, while 14.02% had clear alexithymia. The SMAS-SF total mean score was 73.20±14.59. None of the students reported levels consistent with major social media addiction. The mediated effect of the TAS-20 is about 1.3 times larger than the direct effect of the SMAS-SF on TEQ. Discussion: We found a significant negative correlation between empathy and alexithymia in medical students. Alexithymia was a mediator between social media addiction and empathy. Therefore, we recommend further efforts to identify potential levels of alexithymia in medical students, in order to successfully develop tailored interventions aimed at increasing their emotional awareness.